HUBUNGAN KEMAMPUAN MEMBACA DAN MINAT BACA DENGAN KEMAMPUAN MENULIS KARYA ILMIAH MAHASISWA - Dhimas Asih Kusuma Persadha (Ar-Risalah Media Keislaman Pendidikan dan Hukum Islam, 2018)
This research aimed to observe the relationship reading comprehension skill, reading interest, and reasoning ability toward scientific-papers writing ability. This research uses a descriptive correlational design. The result reveals that (1) there is a significant positive correlation between (a) reading comprehension skill and the scientific-papers writing ability, (b) reading comprehension skill and reading interest toward the scientific-papers writing ability, and (2) there is no a significant positive correlation between reading interest toward the scientific-papers writing ability.